KETAATAN TERHADAP ULU AL-AMR DALAM TINJAUAN HUKUM ISLAM - Seff, Syaugi Mubarak (Fakultas Syariah, 2009)
In the Qur'an there are several verses that teach obedience to the leader (ulu al-amr) as one of the principles value in social life. Obedience to the leader (ulu al-amri) has not been stood alone, but one frame with the obedience to God and His Messenger, in which contains two terms, namely obedience to the commandment of God and obedience to the ordinance of His Messenger (Rasulllah). Obedience to the ulu al-amr has two connotations functional concepts. The two concepts are; first, ulu al-amr as the holders of political power and Moslems as an object of political power.Di dalam al-Qurâ€™an terdapatÂ beberapa ayat yang mengajarkan ketaatan terhadap pemimpin (ulu al-amr) sebagai salah satu dari prinsip yang diperlukan dalam kehidupan bermasyarakat. Ketaatan terhadap ulu al-amr tidaklah berdiri sendiri, tetapi berada dalam bingkai ketaatan terhadap Allah dan Rasul-Nya yang didalamnya mengandung dua pengertian, yaitu ketaatan terhadap apa yang disyariâ€™atkan oleh Allah dan ketaatan tehadap ijtihad Rasulllah. Ketaatan terhadap ulu al-amr memiliki dua konsep yang berkonotasi fungsional. Kedua konsep tersebut ialah ulu al-amr sebagai pemegang kekuasaan politik dan orang-orang mukmin sebagai obyek kekuasaan politik.Keywords: ketaatan, ulu al-amr, dan kekuasaan politik